The Development of Islamic English Register in Pawening Madrassa - Faizal Risdianto (Universitas Veteran Bangun Nusantara, 2020)
This research is descriptive qualitative and has three research objectives: to know the forms of Islamic English Registers, Islamic English Register characteristics and the boosting force and impeding factors of the development of the Islamic English Register at Pawening Madrassa (PM), Surakarta, Indonesia. From the results of observations and interviews it can be seen the results of the study as follows: There was a direct learning strategy using Teacher-Centered-Approach and the